The rostromedial tegmental nucleus modulates the development of stress-induced helpless behavior - Elmer, G.I.; Palacorolla, H.; Mayo, C.L.; Brown, P.L.; Jhou, T.C.; Brady, D.; Shepard, P.D. (Behavioural brain research, 2019)
•Functional changes in the habenula (Hb) are associated with depression.•A major projection from the Hb targets the rostromedial tegmentum (RMTg).•RMTg lesions significantly diminished the expression of stress-induced helpless behavior.•Conversely, increased RMTg activity via Hb stimulation increased helplessness.•The RMTg contributes to stress-induced maladaptive behaviors such as depression. A growing body of clinical and preclinical research suggests that structural and functional changes in the habenula, a component of the epithalamus, are associated with major depressive disorder. A major excitatory, efferent projection from the habenula targets the rostromedial tegmentum (RMTg), a mesopontine region that provides significant input to the ventral tegmentum and raphe nuclei. While the RMTg contributes to monoaminergic responses to aversive events, its role in stress-based animal models of depression has yet to be determined. In the present study, we test the hypothesis that the RMTg is a component of the circuitry mediating the development of a maladaptive behavior in which rats repeatedly exposed to inescapable footshock, fail to avoid or escape the same stressor when subsequently given the opportunity to do so. Excitotoxic lesions of the RMTg significantly diminished the frequency of these escape failures 24 h after exposure to inescapable footshock. Conversely, electrical stimulation of the Hb during the initial uncontrollable aversive event, a manipulation that enhances excitatory input to the RMTg, increased the number of trials in which subjects failed to escape an aversive stimulus when presented the option 24 h later. These complementary results provide evidence supporting a role for the RMTg in the expression of stress-induced helpless phenotype and are an important step in understanding the contribution made by this region to the development of depression-related maladaptive behaviors.